Mesenchymal Stromal Cell-Derived Extracellular Vesicles – Silver Linings for Cartilage Regeneration? - De Luna, Andrea; Otahal, Alexander; Nehrer, Stefan (Frontiers in Cell and Developmental Biology, 2020)
As the world´s population is aging, the incidence of the degenerative disease Osteoarthritis (OA) is increasing. Current treatment options of OA focus on the alleviation of the symptoms including pain and inflammation rather than on restoration of the articular cartilage. Cell-based therapies including the application of mesenchymal stromal cells (MSCs) have been a promising tool for cartilage regeneration approaches. Due to their immunomodulatory properties, their differentiation potential into cells of the mesodermal lineage as well as the plurality of sources from which they can be isolated, MSCs have been applied in a vast number of studies focusing on the establishment of new treatment options for Osteoarthritis. Despite promising outcomes in vitro and in vivo, applications of MSCs are connected with teratoma formation, limited lifespan of differentiated cells as well as rejection of the cells after transplantation, highlighting the need for new cell free approaches harboring the beneficial properties of MSCs. It has been demonstrated that the regenerative potential of MSCs is mediated by the release of paracrine factors rather than by differentiation into cells of the desired tissue. Besides soluble factors, extracellular vesicles are the major component of a cell´s secretome. They represent novel mechanisms by which (pathogenic) signals can be communicated between cell types as they deliver bioactive molecules (nucleic acid, proteins, lipids) from the cell of origin to the target cell leading to specific biological processes upon uptake. This review will give an overview about extracellular vesicles including general characteristics, isolation methods and characterization approaches. Furthermore, the role of MSC-derived extracellular vesicles in in vitro and in vivo studies for cartilage regeneration will be summarized with special focus on transported miRNA which either favored the progression of OA or protected the cartilage from degradation. In addition, studies will be reviewed investigating the impact of MSC-derived extracellular vesicles on inflammatory arthritis focusing especially on the modulation of inflammatory cells. As extracellular vesicles are present in all body fluids, their application as potential biomarkers for OA will also be discussed in this review. Finally, studies exploring the combination of MSC-derived extracellular vesicles with biomaterials for tissue engineering approaches are summarized.